The Implementation of Restorative Justice by Indonesian National Police Investigators in Traffic Accidents Resulting in Death - Budi Utomo (IJCLS (Indonesian Journal of Criminal Law Studies), 2018)
criminal justice system from investigation, prosecution, trial examination and execution of judgment which leads to criminalization, but in its development there is an alternative law enforcement desired by the justice seekers through restorative justice which prioritizes recovery at the original state as a result of the crime. Therefore, it is necessary to analyze the importance of restorative justice by Indonesian National Police Investigators in traffic accidents resulting in death, as well as its implementation. The theoretical concepts used are implementation, restorative justice, law enforcement, criminal law policy, justice, traffic accidents, and Police Investigators. Qualitative research approach, type of socio-juridical research, focuses on the importance of restorative justice and its implementation by Indonesian National Police Investigators in traffic accidents resulting in death. Location of research is in Resort Police of Semarang. Data sources are primary, secondary and tertiary. Data collection techniques were conduct through documentation, observation, and interviews. Data validity was using triangulation technique, data analysis technique using interaction analysis model. The results of research on the importance of restorative justice and its implementation by Indonesian NationalÂ Police Investigators in traffic accidents resulting in death are analyzed through philosophical, sociological and juridical point of view, while its implementation is analyzed by the implementation model of George C. Edward III which shows that restorative justice has not been understood optimally by Indonesian National Police investigators and the community even though in reality have been practiced in the duties or daily life. The obstacles, namely the absence of legal restorative justice umbrella is firm and clear, still weak understanding of Indonesian National Police Investigators and the public, especially the parties related to the settlement of criminal cases through restorative justice. Efforts to overcome these obstacles, Police Investigators in the settlement of criminal acts through restorative justice refers to the rules that are directly or indirectly relevant, organizing socialization about restorative justice within the Indonesian National Police, especially Indonesian National Police Investigators, and the public. Based on the description above, it can be concluded that the importance of restorative justice can be seen from philosophical, sociological and juridical point of view, whereas in its implementation is influenced by four factors, namely, communication, resources, disposition, and bureaucratic structure. Suggestion of clear and firm regulation related to settlement of criminal case through restorative justice, especially traffic accident and the need to increase understanding of restorative justice by Indonesian National Police personnel, especially Indonesian National Police Investigator and society in general.